2012
DOI: 10.1590/s1516-35982012000200024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cornell Net Carbohydrate and Protein System model on the prediction of dry matter intake and milk production of grazing crossbred cows

Abstract: -The Cornel Net Carbohydrate and Protein System model version 5.0 was assessed as for its prediction of dry matter intake and milk production of grazing lactating Holstein × Zebu cows. Eight lactating cows grazing elephant grass (Pennisetum purpureum, Schum., cv. Napier) were used in two experiments of 30 days each. The experimental design was of randomized blocks (subplots). Dry matter intake was estimated using the chromium oxide and in vitro dry matter digestibility techniques. The estimated dry matter inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…These values were lower than those reported by Morenz et al (2012) with Napier grass managed under rotational stocking with a rest period of 30 days during the rainy season. Also, lignin contents varying from 5.1 to 7.6% were related to different elephantgrass cultivars (LIMA et al, 2008;VOLTOLINI et al, 2010;MORENZ et al, 2012). The results reported in the present study confirm the low lignin contents found by Madeiro (2010), who evaluated the same elephantgrass clones in the previous year.…”
Section: Grazing Cycles Sem (1)contrasting
confidence: 74%
“…These values were lower than those reported by Morenz et al (2012) with Napier grass managed under rotational stocking with a rest period of 30 days during the rainy season. Also, lignin contents varying from 5.1 to 7.6% were related to different elephantgrass cultivars (LIMA et al, 2008;VOLTOLINI et al, 2010;MORENZ et al, 2012). The results reported in the present study confirm the low lignin contents found by Madeiro (2010), who evaluated the same elephantgrass clones in the previous year.…”
Section: Grazing Cycles Sem (1)contrasting
confidence: 74%
“…However, this was not the case for indigofera in which it contained higher ADF than that of papaya but had gas production as well. It might be that other factors influencing gas production were present such as different types of carbohydrate, degradability and fermentability of carbohydrate under ruminal environment (Morenz et al, 2012) and antinutritive compounds (Laconi and Widiyastuti, 2010;Kondo et al, 2014), in which these parameters were not measured in the present experiment. Lower gas production after ensiling treatment apparently related to partial utilization of water soluble carbohydrate by lactic acid bacteria and other microorganims present in silage, thus contributing to a reduced gas production.…”
Section: In Vitro Rumen Fermentation and Digestibilitymentioning
confidence: 85%